The BDNF-TrkB Pathway Acts Through Nucleus Accumbens D2 Expressing Neurons to Mediate Stress Susceptible Outcomes - Pagliusi, Marco; Franco, Daniela; Cole, Shannon; Morais-Silva, Gessynger; Chandra, Ramesh; Fox, Megan E.; Iñiguez, Sergio D.; Sartori, Cesar R.; Lobo, Mary Kay (Frontiers in Psychiatry, 2022)
Brain-derived neurotrophic factor (BDNF) has a critical role in stress response including neuropsychiatric disorders that are precipitated by stress, such as major depressive disorder (MDD). BDNF acts through its full length BDNF receptor, tyrosine kinase B (TrkB), to trigger a pro-plasticity effect. In contrast, the truncated isoform of the BDNF receptor (TrkB.t1) triggers an anti-plasticity effect. In stress outcomes, BDNF acting in the hippocampus has a stress resilient effect, whereas BDNFin the nucleus accumbens (NAc) promotes stress susceptibility. It is unknown if BDNF-TrkB acts on a specific NAc projection subtype or medium spiny neuron (MSN) subtype , in stress outcomes. To determine this, we performed chronic social or a vicarious witness defeat stress (CSDS or CWDS) in mice expressing TrkB.t1 in dopamine receptor 1 or 2 containing MSNs (D1- or D2-MSNs). Our results showed that TrkB.t1 overexpression in NAc D2-MSNs prevented the CSDS-induced social avoidance or other stress susceptible behaviors in male and female mice. Further, we showed that this overexpression in D2-MSNs blocked stress susceptible behavior induced by intra-NAc BDNF infusion. In contrast, our results demonstrate that overexpression of TrkB.t1 on NAc D1-MSNs facilitates the SDS susceptible behaviors. Our study provides enhanced understanding ofNAc cell subtype roles of BDNF-TrkB signaling in stress outcomes.